2003
DOI: 10.1016/s1010-7940(03)00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative comparison of different transient external shunt techniques in bidirectional cavo-pulmonary shunt

Abstract: Based on the study presented here, bidirectional cavo-pulmonary anastomosis can be carried out by using different types of transient external shunt. The best hemodynamical condition and arterial O(2) levels were achieved with the shunt constructed between superior vena cava and left pulmonary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…[3] Although some advocated this procedure through right thoracotomy, we often prefer median sternotomy which has the advantages of better exposure and rapid institution of CPB in case of emergency. [2,3] Avoidance of CPB and aortic cross clamping has the advantages including earlier extubation, less blood products, reduced necessity and duration of inotropic support. Some authors have demonstrated increased pulmonary vascular resistance and hypoxia after CPB and possible development of aortopulmonary shunts after establishing CPB, leading to prolonged pleural effusions.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Although some advocated this procedure through right thoracotomy, we often prefer median sternotomy which has the advantages of better exposure and rapid institution of CPB in case of emergency. [2,3] Avoidance of CPB and aortic cross clamping has the advantages including earlier extubation, less blood products, reduced necessity and duration of inotropic support. Some authors have demonstrated increased pulmonary vascular resistance and hypoxia after CPB and possible development of aortopulmonary shunts after establishing CPB, leading to prolonged pleural effusions.…”
Section: Discussionmentioning
confidence: 99%
“…It may also lead to eddy currents and subsequent thrombus formation. 6 We have realized that median sternotomy approach for constructing BD Glenn shunt has the advantage of allowing a precise anastomosis being constructed, easy conversion if CPB is required, minimal interference with ventilation, which maintains good oxygen saturation during the procedure. Though there are cardiac surgical units that perform this procedure through right thoracotomy, 5 we preferred a median sternotomy, as our concern was both proper alignment of BD Glenn shunt through thoracotomy route and known hazardous effect of SVC clamping without use of CPB.I.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are cardiac surgical units that perform this procedure through right thoracotomy, 5 we preferred a median sternotomy, as our concern was both proper alignment of BD Glenn shunt through thoracotomy route and known hazardous effect of SVC clamping without use of CPB.I. 6 We feel the decompression of the SVC provides more safety margin and assures sufficient cardiac output, which in turn maintains optimal oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first description by Glenn 1 this operation has undergone a variety of modifications and is commonly performed using continuous cardiopulmonary bypass (CPB) with satisfactory early and long-term results 2 . Various groups have advocated performing this operation without CPB and have claimed it to be advantageous [3][4][5][6][7][8][9][10][11] . In this report, we discuss the evolution of the techniques of BCPS without CPB and present details of our preferred technique of performing this operation in a reproducible manner.…”
Section: Introductionmentioning
confidence: 99%